Pengaruh Tarif Pajak Dan Struktur Aktiva Terhadap Struktur Modal - Sari, Maya; Moh. Yuddy Yudawirawan (EkoPreneur, 2025)
This study was conducted with the aim of analyzing the effect of tax rates and asset structure on capital structure. The object of the research is focused on companies classified under the Consumer Non-Cyclicals sector and listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample selection was carried out using a purposive sampling method, resulting in eight companies that met the specified criteria. The data used in this study are secondary data in the form of audited annual financial statements obtained from the official website of the IDX. The analytical method employed is multiple linear regression, which is supported by both simultaneous tests (F-test) and partial tests (t-test) to examine the significance of the independent variables on the dependent variable. Furthermore, a series of classical assumption tests were performed, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, in order to ensure the validity and reliability of the regression model. The findings of the analysis reveal that tax rates and asset structure simultaneously have a significant effect on capital structure, which highlights the importance of fiscal policy and asset composition in determining financing decisions. However, the results of partial testing provide different insights. Tax rates do not have a significant effect on capital structure, implying that variations in tax obligations are not a dominant consideration for companies when formulating financing policies. Similarly, asset structure does not show a significant partial effect, suggesting that the proportion of fixed and current assets is not an independent determinant of capital structure decisions. Overall, these results indicate that other factors beyond tax rates and asset structure may play a more influential role in shaping capital structure within Consumer Non-Cyclicals companies. Keywords: Tax Rates, Asset Structure, Capital Structure